Long-term metabolic changes with bictegravir/emtricitabine/tenofovir alafenamide or dolutegravir-containing regimens for HIV - Eric S. Daar; Chloe Orkin; Paul E. Sax; Debbie Hagins; Anton Pozniak; Kimberly Workowski; Cynthia Brinson; Juan Manuel Tiraboschi; Hui Liu; Chris Deaton; Cal Cohen; Sharline Madera; et al. (AIDS Research and Therapy)
Abstract Background To evaluate long-term changes in weight and metabolic parameters in people with HIV-1 (PWH) initiating first-line antiretroviral therapy. Methods Analysis of two Phase 3, randomized, double-blind, active-controlled trials (1489: NCT02607930; 1490: NCT02607956). PWH received bictegravir/emtricitabine/tenofovir alafenamide (B/F/TAF) or dolutegravir (DTG)-based treatment (Study 1489: dolutegravir/abacavir/lamivudine [DTG/ABC/3TC]; Study 1490: DTG + F/TAF) for 144 weeks, followed by B/F/TAF (96-week open-label extension up to Week 240). Weight and metabolic parameters were assessed through Week 144 by randomized treatment assignment. Weight changes by baseline viral load and CD4 count were evaluated in PWH receiving B/F/TAF from baseline through Week 240. Multivariate modeling explored baseline factors associated with absolute weight and weight change through Week 240 and weight gain ≥ 10% at Week 240. Results Median weight and body mass index (BMI) increased over time with B/F/TAF (n = 628), DTG/ABC/3TC (n = 315), and DTG + F/TAF (n = 325). There were no significant differences in change in weight or BMI between the B/F/TAF and DTG + F/TAF groups or between the B/F/TAF and DTG/ABC/3TC groups at Week 144 in either trial, nor were there differences in other metabolic parameters, including incidence of treatment-emergent diabetes mellitus and hypertension through Week 144. Among PWH receiving B/F/TAF (baseline through Week 240), weight increases were greatest soon after initiating antiretroviral therapy (i.e., Weeks 0–48), particularly in participants with baseline viral load > 100,000 copies/ml and/or CD4 count < 200 cells/µl. In multivariate modeling (B/F/TAF pooled data), lower baseline CD4 count and higher HIV-1 RNA were associated with lower baseline weight and greater weight gain, but not absolute weight, from Week 48 through Week 240. Conclusions No significant difference in weight change from baseline to Week 144 was found between bictegravir and DTG, or between B/F/TAF and a non-TAF-containing regimen, in these two randomized trials. Furthermore, weight gain following treatment initiation was greatest in the first year of treatment and most pronounced in individuals with more advanced HIV at baseline, supporting the hypothesis that weight gain following initial treatment is linked to a “return to health” in people with advanced HIV.